Artur Mezglewski, Anna Tunia, Wyznaniowa forma zawarcia małżeństwa cywilnego, 2007 - Fastyn, Arkadiusz (Czasopismo Prawno-Historyczne, 2018)
Artur Mezglewski, Anna Tunia, Wyznaniowa forma zawarcia małżeństwa cywilnego, 2007